A Fast-k(z) 3D Tailored RF Pulse for Reduced B1 Inhomogeneity - Saekho, Suwit (2006)
This paper presents a small-flip-angle, three-dimensional tailored RF pulse that excites thin slices with an adjustable quadratic in-plane spatial variation. The quadratic spatial variation helps to compensate for the loss in image uniformity using a volume coil at 3T due to the wavelike properties of the RF field. The pulse is based on a novel “fast-k(z)” design that uses a series of slice-select sub-pulses along k(z) and phase encoding “blips” along k(x)-k(y). The method is demonstrated by acquiring a series of 5 mm thick T2-weighted images of the human brain at 3T using pulses 4.8 ms in length with a 45° flip angle.